Interest Students to be Productive Teachers Reviewed from Learning Achievement of Building Practices, Learning Achievement of Learning Practices and Learning Motivation - Sukendar, Sukendar; Endroyo, Bambang; Sudarman, Sudarman (Journal of Vocational and Career Education, 2018)
Interest is one of the most important psychological factors for human progress and success in a person. Some factors from the inside that influence such as emotional factors, motivation, talent, intelligence, mastery of science in the form of learning achievements and field practice experience. The problems studied in this research are: (1) are there any influence of building practice achievement toward student interest S1 PTB FT Unnes become productive teacher? (2) are there any influence of teaching practice achievement toward student interest S1 PTB FT Unnes become productive teacher? (3) are there any influence of learning motivation toward student interest S1 PTB FT Unnes become productive teacher ?; and are there influence of building practice achievement, achievement of teaching practice and motivation learn to student interest S1 PTB FT Unnes meniadi teacher productive? The research approach used ex-post-facto because the researcher did not give any treatment to the research subject. The sample that used is the student of FT Unnes Building Technical Education Undergraduate Program semester VII which participated in PPL Semester Gasal 2016, as many as 40 people. The analysis tool uses validity and reliability test, classical assumption test, multiple linear regression test, t test, F test and coefficient of determination. The results showed that the achievement of building practice, the achievement of teaching practice and the motivation to learn simultaneously or partially have a positive influence on the interest to become productive teachers. Suggestions that can be stated that the students need to be more serious in conducting the practice of building that is by asking things that are not understood to the supervisor. Students need to foster seriousness and commitment to practice teaching activities. Students need to grow the desire to succeed.